USING ANALGESICS IN DIFFERENT AGE GROUPS, INCLUDING INTERGENERATIONAL RELATIONS - Marcin Weiner; Małgorzata Tokarska-Rodak (Rozprawy Społeczne)
Introduction In spite of the restrictions associated with the sale of medicinal products over the past 8 years, the over-the-counter drug sales have nearly doubled. This is caused by a broad access to pharmaceuticals, abandonment of professional medical advice, and too many long queues to the general practitioner.